(untitled) (Applied Biological Research, 2015)
The present paper describes a sandwich non-competitive enzyme-linked immunosorbant assay (ELISA) for erythropoietin (EPO). The ELISA utilizes a specific polyclonal antibody raised in rabbit against human recombinant EPO (rhu EPO). Anti-EPO was coated onto 96-well micro titer plate, standard EPO or samples were added and left to bind to this catching antibody. This was followed by the addition of same antibody, which was conjugated with horse-radish peroxidase (HRP); and the enzyme reaction developed was measured at 450 nm. Recombinant human EPO was standardized against WHO 2nd International Reference Preparation for Erythropoietin. The minimal detectable concentration of rhu EPO was 20 pg mL-1, which corresponded to 80 pg mL-1 EPO in serum (serum diluted 1:4). The assay is easy to use, rapid, reproducible and quantitative, specific and sensitive to measure EPO content in serum samples.